ANALISIS PENINGKATAN FASILITAS KESEHATAN DAN PELATIHAN TENAGA MEDIS DALAM MENDUKUNG PROGRAM KESEHATAN IBU DAN ANAK: KAJIAN PUSTAKA - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
Maternal and child health is a crucial aspect of quality human resource development. This study aims to analyse improvements in health facilities and medical personnel training as key factors in supporting the success of maternal and child health programmes in Indonesia. The method used is a literature review, examining various scientific literature, policy reports, and relevant documents. The findings indicate that adequate improvements in healthcare facilities and continuous training for medical personnel significantly contribute to reducing maternal and infant mortality rates. However, challenges such as uneven distribution of facilities and limited human resources still need to be addressed. This study recommends strengthening programmes through service innovation, equitable distribution of facilities, and competency-based training that is responsive to field needs. Policy support and community participation are supporting factors for the sustainability of improvements in maternal and child health.